Terrorism: what the statistics show / Mokhtar Muhammad and Haliza Hasan - Muhammad, Mokhtar; Hasan, Haliza (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Terrorism has been widely used as a tool by extremists to achieve their goals. Terrorists consider themselves as freedom fighters to liberate the socalled "oppressed" people. The destructions caused by terrorists are enormous where many lives perished in this "holy war". How the media cover the acts of terrorism actually differ and varied according to their media policy on how they want to present the terrorist stories in their news reporting especially for the headlines. Like what has been stated earlier, there are two types of media coverage of terrorism namely as pro- errorist and anti-terrorist. Nowadays, international media especially the Western cable is pro-terrorist press as they believed terrorism news will increase their readership and profit. Without realizing it, they actually trigger and developed the fear of Islam within the world society, as most of them labeled Muslim or Islam as terrorists. This study is based on secondary data to look at the phenomenon of terrorism throughout the world. Descriptive statistics are used to describe and to summarize the acts of terrorism. The statistics on terrorism include the incident information, incident location, attack information, weapon information, target/victim information, perpetrator information, casualties, and consequences. The statistics are summarized using an existing database managed by the University of Maryland, USA, which is named as the Global Terrorism Database (GTD). Information on terrorist attacks captured were incidences in the period of 1970 to 2015. The GTD includes systematic data on domestic as well as transnational and international terrorist incidents that have occurred during this period and contain more than 140,000 cases. The study uses descriptive information about the incidences of terrorism, to show dominant features on certain variables such as attack information or group information, as well as how these dominant features connect with the rest of the variables in the database.